Heat Induced Passivation of CuInSe2 Surfaces: A Strategy to Optimize the Efficiency of Chalcopyrite Thin Film Solar Cells?. Issue 2 (13th January 2014) - Mönig, Harry; Lockhorn, David; Aghdassi, Nabi; Timmer, Alexander; Kaufmann, Christian A.; Caballero, Raquel; Zacharias, Helmut; Fuchs, Harald
<x xml:space="preserve">Abstract</x> Despite the success of chalcopyrite thin film solar cells, many open questions are related to the complex defect physics at the interface between the n‐type window layer and the p‐type chalcopyrite absorber, which largely determines the device efficiency. Therefore, this study aims to clarify the defect physics of chalcopyrite thin film surfaces, which is investigated by scanning tunneling spectroscopy, photoelectron, and inverse photoelectron spectroscopy. After removing surface oxides by a wet chemical KCN treatment and subsequent annealing at 280 °C in ultrahigh vacuum, a complete passivation of defect levels is observed, which goes along with a type inversion and an enlarged band gap at the surface. Therefore, this sample state consolidates three exclusively beneficial properties, which potentially minimize interface recombination losses and increase the open circuit voltage in completed devices. In contrast, oxidation of the surface by annealing in air reduces the surface band bending and creates a high density of charge compensated defect levels, implying exclusively detrimental effects on the device performance due to the presence of oxygen at the window/absorber heterojunction. These results are discussed in view of previous models suggesting a passivation of defect levels upon oxygenation of the interface.